Computational and experimental investigation of laminar flow mixing system in a pitched-blade turbine stirred tank - Cui, Yanyan; Zhang, Huabo; Li, Xiwen; Yang, Mingjin; Guan, Zailin (International Journal of Agricultural and Biological Engineering, 2018)
The flow distribution and mixing performance of the laminar flow in the PBT impeller-stirred tank were investigated in this study. The variation along with mixing time of the flow distribution and concentration at the selected positions was visualized by means of the CFD and experiment methods. The CFD simulations results had a good agreement with the experimental results. In order to minish the Segregated Regions, the PBT impeller was optimally designed by means of orthogonal factorial experiment with selecting the θ99 mixing time as evaluation criteria. With the aim to increase the mixing efficiency, the optimal design results were obtained with the geometrical parameters of impeller diameter of 0.084 m, discharge angle of 45º, blade width of 0.018 m, and clearance of 0.05 m, and the mixing time of the optimal impeller-stirred flow was about 180 s, so this optimal design PBT impeller is more proper for the agricultural industries. Keywords: mixing, laminar flow, PBT impeller, mixture homogeneity, CFD DOI: 10.25165/j.ijabe.20181104.2729 Citation: Cui Y Y, Zhang H B, Li X W, Yang M J, Guan Z L. Computational and experimental investigation of laminar flow mixing system in a pitched-blade turbine stirred tank. Int J Agric & Biol Eng, 2018; 11(4): 111-117.